2019
DOI: 10.1634/theoncologist.2019-io-s1-s02
|View full text |Cite
|
Sign up to set email alerts
|

Retrospect and Prospect for Lung Cancer in China: Clinical Advances of Immune Checkpoint Inhibitors

Abstract: This review summarizes the developmental process of immunotherapy in lung cancer, ongoing international and domestic clinical trials in the field, and the challenges related to immunotherapy in the lung cancer patient population in China. The goal is to provide detailed information for future immunotherapy‐related clinical trials in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…In addition, the Chinese government has listed lung cancer as a focus of future cancer prevention and treatment. 4 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Chinese government has listed lung cancer as a focus of future cancer prevention and treatment. 4 …”
Section: Introductionmentioning
confidence: 99%
“…EGFR-TKIs are more effective for patients with EGFR mutant lung cancer than platinum-based chemotherapy (8). Erlotinib as a kind of EGFR-TKIs, is clinically effective for the treatment of NSCLC (9). According to Korytowsky et al (10), there is no significant difference in efficacy between erlotinib and chemotherapy (docetaxel or pemetrexed) for patients with advanced NSCLC who have received platinum-based chemotherapy for no more than 4 cycles and have disease progression during or after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignant tumors and causes more cancer deaths per year than the next three cancers combined in China. Despite remarkable advances in targeted therapy, the morbidity and mortality of lung cancer still have not significantly improved worldwide (Lu, Yu & Yang, 2019; Wang et al, 2019). Statistics from GLOBOCAN 2012, produced by the International Agency for Research on Cancer (IARC), indicated that approximately 1.8 million new cases of and approximately 1.6 million deaths from lung cancer each year (Torre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%